STUDI TEGANGAN-REGANGAN SALOK ( Tinjauan Terhadap Konstruksi Ramp Stadion Maguwoharjo, Sleman ) - Pramudiyanto Pramudiyanto (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
AbstractThis research aims to gather information of computer application ofstructural mechanics to determine the distribution of stress and strain ofthe cross section. The research focuses on the actors of computer users,the data analyzing, and stress-strain behavior.This research applies experimental approach. The chosensubject is the ramp construction of The Maguwoharjo Soccer Stadium,Sleman. The construction is being chosen with the reason of a uniqueconstruction.The ramp then being analyzed mathematically usingVisualFEA to determined the stress-strain behavior.The research result show that the use of specific computerprograms, and for the specific case given, the distribution of stress andstrain still linear. The analysis show that the distribution of stress stillfollow the linearity, even the analysis method using the different way.Keywords: computer user, structural mechanics, stress-strain.